Gö6983 attenuates breast cancer‐induced osteolysis by the apoptotic pathway. (26th December 2019) - Luan, Zhiwei; Li, Jia; Huang, Xing; Feng, Wenyu; Ma, Shiting; Song, Fengyang; Wu, Zhengyuan; Zhang, Xiaohan; Wei, Linfeng; Yang, Zhenyi; Yao, Jun
Abstract: Bone metastasis caused by breast cancer leads to significant complications in treatment, and the resulting osteolysis considerably affects patients' overall survival and quality of life. Gö6983 is a broad spectrum protein kinase C inhibitor. In this study, based on our finding that the Gö6983 inhibits osteolysis, we applied Gö6983 to the MDA‐MB‐231 breast cancer‐induced mouse bone metastasis model. And we found that Gö6983 has a strong inhibitory effect on the tumorigenic model of breast cancer by promoting the mitochondrial apoptosis pathway. Our study, therefore, demonstrates that Gö6983 has a potential inhibitory effect on breast cancer‐induced osteoclast activation and provides mechanistic insight that may prove useful for designing future treatments.